Pemahaman Masyarakat Pada Pelaksanaan Sertifikat Tanah Wakaf Dalam Kajian Manajemen Wakaf ( Studi Kasus Di Kantor Urusan Agama Sako Kota Palembang ) - ., Risky; ., Lemiyana; Pratama , Chici Rima Putri (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research is entitled "Community's Understanding of the Implementation of Waqf Land Certificates in the Study of Waqf Management (Case Study at the Sako Religious Affairs Office, Palembang City)." Waqf is a form of worship whose practice will not be interrupted even after a person dies, namely waqf. For Muslims, the term waqf is certainly familiar. Waqf is often equated with almsgiving. The property usually donated is land. Waqf can be briefly defined as property donated in the way of Allah to be utilized by the public. This research was conducted at the Sako District Religious Affairs Office, Palembang City. In this research the author used a qualitative method with a descriptive approach. The author also used several data collection techniques, namely observation, interviews and documentation. The results of this research are that the level of public understanding regarding the implementation of waqf land certification still does not understand waqf land certification. The community has different views regarding waqf land certification. As for the implementation of waqf land certification in the KUA, Sako District, Palembang City, it has been carried out, but there is still a lack of public understanding of the obstacles related to financing waqf land certification, there are also other obstacles in carrying out waqf land certification, such as, the public still does not understand the flow of waqf land certification and lack of socialization from the Palembang city government.